التنظيم القانوني الدولي لحق اللجوء وموقف الشريعة الإسلامية منه (دراسة تحليلية) - لؤي عبد الكريم سلطان
The study focuses on the phenomenon of asylum and the increasing in the number of refugees in the world. This phenomenon has been considered as one of the contemporary problems facing the international community because it reflects the humanitarian, legal, political, social and economic human problem. It also considered a problem facing both the individual and the Nations. Hence, this study attempts to examine the issue of asylum under the international public law. As such, the study tries to answer these four research questions. First, what is the definition of asylum in international law and Islamic law, and its similarity in the Quran and Sunnah? Second, what is the constitutional and Islamic right for the asylum seeker been a foreigner, a potential refugee in a new society, and its right to choose the nation he/she wants to seek refuge; thirdly, what are the mechanisms refugees’ protection in term of International and Islamic laws. Fourth, what are the most important role played by the International and Regional Organizations and International Non-Governmental Organizations in refugees’ protection? Therefore, the study investigated the determining movements of irregular refugees according to the principle of the country of first refuge, and the refugee rights and duties under international law. Also, the study addressed the position of Islamic law and the extent of recognition of the refugee’s right, such as seeking protection and establishment the foundations of legal legitimacy. Refugee has his/her own rights, irrespective of his/her religion, being a Muslim or polytheist. As it has made it an obligation, refugee must not be handed over to his country of origin or any other nation that he is fearing for his life or violation of his basic rights without his consents. The research also discussed the international Non-Governmental Organizations and their role in protection refugees. Hence, the study adapted critical analytical method to examine conventions, charters and the international and regional declarations since the founding of the United Nations until 2112 AD. The study found that the International community realized the need to cooperate and unite the efforts to face the phenomenon of asylum after the waves of asylum that swept the world. Also, it also realized that the role of the International community should not be limited to non-binding recommendations and decisions, as in the World agreement in 2112. It was also found that Islamic law has formulated basic rules for asylum which has been recognized by contemporary International law in many of the provisions associated with it. And that the role played by international and regional organizations and non-governmental organizations, as laid down in international conventions and conventions, exists and is effective.